Compra de brinquedos para a primeira infância: estudo sobre os fatores de influência na decisão de compra - Leite, Carolina Cristina Marques (2018)
The traditional toys market on the one hand takes advantage of the strength of brands and known characters using licenses in their products. On the other hand, no licensed toys fight on the shelves of stores for the preference of that child or adult who is deciding which one to buy. So, at this point the industry asks itself: to the child or the adult, what are the main reasons for choosing toys? Beyond to this question, the objective of this study is to understand the dynamics of the process of buying toys for infants and their influence factors. The methods used were qualitative research, from field observation in 23 toy stores in different Brazilian cities and quantitative from the application of structured questionnaire (survey). The subjects are consumers of toys, mostly parents of children between 0 and 6 years old. The interpretation of the collected material followed the precepts of content analysis. The main results were observers and interviewees believe that the toy plays a fundamental role in the education of children, although, in this study, the concept of education seems to be related only to formal education, given the frequency of buying off special occasions. The consumers are doubtful when choosing which toy to buy and recognize that at certain times they buy those that are not educational. In conclusion, the industry and toy brands study this market, however, they do not exploit the educational attributes of toys regarding to the developmental phases of the child at this stage of life (up to 6 years old). The lack of information in the media, shops and packaging prompts the consumer to doubt when choosing.